Odpowiedzi

Najlepsza Odpowiedź!
2009-11-19T15:55:46+01:00
A) 4y - x = 6
17y = 0 /:17
4y - x = 6
y = 0
4 * 0 - x = 6
y = 0
-x = 6/: (-1)
y = 0
x = -6
b)
a = b
2a + b = 9
a = b
2b + b = 9
a = b
3b = 9 /: 3
a=b
b = 3
a = 3
c)
u = 4v
5u - v = 10
u = 4v
20v - v = 10
u = 4v
19v = 10/ :19
u = 4v
v = 1,9
u = 7,6
d)
3r = s
3r + s = 24
3r = s
3r + 3r = 24
3r = s
6r = 24/:6
3r = s
r = 4
s = 12
2009-11-19T16:05:40+01:00
A)
4y-x=6
17y=0

4y - x = 6
17y = 0 /:17

4y - x = 6
y = 0

4 * 0 - x = 6
y=0

y = 0
-x = 6/: (-1)

y = 0
x = -6



b)
a=b
2a+b=9

a-b=0/*(-2)
2a+b=9

-2a+2b=0
2a+b=9
__________

3b=9/:3
b=3

a-b=0
a-3=0
a=3

a=3
b=3




c)
u=4v
5u-v=10

u=4v
5(4v)-v=10

u=4v
20v-v=10

u=4v
19v=10/:19

u=4v
v= 10/19

u=4* 10/19
v=10/19

u=40/19
v=10/19

u= 2 2/19
v=10/19



d)
3r=s
3r+s=24

s=3r
3r+3r=24

s=3r
6r=24/:6

s=3r
r=4

s=3x4
r=4

s=12
r=4